QUALITY–QUANTITY DECOMPOSITION OF INCOME ELASTICITY OF U.S. HOSPITAL CARE EXPENDITURE USING STATE‐LEVEL PANEL DATA1. (19th August 2013) - Chen, Weiwei; Okunade, Albert; Lubiani, Gregory G.
SUMMARY Economic theory suggests that income growth could lead to changes in consumption quantity and quality as the spending on a commodity changes. Similarly, the volume and quality of healthcare consumption could rise with incomes because of demographic changes, usage of innovative medical technologies, and other factors. Hospital healthcare spending is the largest component of aggregate US healthcare expenditures. The novel contribution of our paper is estimating and decomposing the income elasticity of hospital care expenditures (HOCEXP) into its quantity and quality components. By using a 1999–2008 panel dataset of the 50 US states, results from the seemingly unrelated regressions model estimation reveal the income elasticity of HOCEXP to be 0.427 (std. error = 0.044), with about 0.391 (calculated std. error = 0.044) arising from care quality improvements and 0.035 (std. error = 0.050) emanating from the rise in usage volume. Our novel research findings suggest the following: (i) the quantity part of hospital expenditure is inelastic to income change; (ii) almost the entire income‐induced rise in hospital expenditure comes from care quality changes; and (iii) the 0.427 income elasticity of HOCEXP, the largest component of total US healthcare expenditure, makes hospital care a normal commodity and a much stronger technical necessity than aggregate healthcare. Policy implications are discussed. Copyright © 2013 John Wiley & Sons, Ltd.